Human Life as a Basic Good: A Dialectical Critique (2016)
In this article I argue that the fundamental axiological claim of the New Natural Law Theory, according to which human life has an intrinsically valuable, cannot be defended within the framework assumed by the New Natural Law Theory itself, and further, that such a claim turns out to be false relative to a wider eudaimonistic framework that the Natural Law theorist is committed to accept. I do this this by adopting a dialectical standpoint which excludes any assumptions that could be de-nied by the New Natural Law theorist, except for the axiological claim, and show that the New Natural Law theorist cannot argue for the axiological claim’s plausibility, and moreover, that in such a setting the New Natural Law theorist is compelled to replace the axiological claim by the claim that human life is instrumentally valuable.